Foodborne illness from tuba-tuba seeds among school-aged children, Philippines: a call for community education - Venturina, Darren H; Agulto, Apple Charm A; Faiyaz MF, Alireza S; Ventura, Ray Justin C; Blanco-Payuyo, Mariz Zheila C; Roca, John Bobbie (Western Pacific Surveillance and Response, 2025)
Objective: On 2 September 2023, the Regional Epidemiology and Surveillance Unit of the Department of Health’s Center for Health Development in Calabarzon, Philippines, received a report of foodborne illness due to the ingestion of tuba-tuba (Jatropha curcas) seeds in Talao Talao Village, Lucena City. The objective of this study was to describe the public health event. Methods: A descriptive study was conducted. Cases were defined as previously well individuals who developed at least one of the following symptoms after eating tuba-tuba seeds: vomiting, abdominal pain, diarrhoea, headache or dizziness. Health records were reviewed, and key informant interviews and environmental surveys were conducted. Results: Ten cases were identified, ranging in age from 10 to 12 years. The onset of symptoms ranged from 1 to 4 hours after consumption. Six of the cases were taken to the hospital, although two went home before being admitted; all recovered after 3 days. The most common symptom was vomiting (100%); other symptoms included abdominal pain, diarrhoea, dizziness and headache. Discussion: This investigation confirmed that tuba-tuba seeds were the cause of symptoms among school-aged children in Lucena City. To prevent similar events in the future, we recommend intensifying educational campaigns at both the community and school levels, as tuba-tuba is common in the area.